(untitled) (International Journal of Ayurveda and Pharma Research, 2020)
The changing lifestyle and dietary pattern has given way to many gynecological problems in females. Uterine fibroids are one of leading concerns for women in reproductive age. Though uterine fibroids are non- cancerous in character; they exhibit a wide range of symptoms like dysmenorrhea, menorrhagia, metrorrhagia, low backache etc. It significantly hampers the general health and quality of life in women causing great mental agony. Contemporary treatment protocols include hormonal therapy, hysterectomy, myomectomy and uterine artery embolization. Reluctance to undergo prolonged hormone therapy, the fear of surgery brings more and more patient to Ayurveda. Hence more systematic studies in conservative management in these areas of Stree Roga are need of the hour. Ayurveda classics mention various pathological conditions that have features similar to fibroids. Owing to its muscular origin, with slow growth may be better compared to Granthi in Garbhasya. In the modern era of busy lifestyle, intake of junk food, lack of exercise etc had lead to Agnivaishamya and Ama formation. This in turn vitiates Doshas like Kapha and Vata and Dushyas like Rasa, Raktha, Mamsa, Medas and Arthava resulting in Dhatwagnimandya leading to formation of Garbhasayagranthi. The treatment approach is directed towards reducing size of fibroids using Ushna, Tiskhna, Lekhana Dravyas along with management of symptoms. The inevitable roles of Vata in Yoniroga is also taken into account in its management. Combining different treatment aspects of Granthi and Yoni Roga Chitksa, a unique approach towards the management of its varied presentations added on with lifestyle modification can contribute to healthy social life. The current article focuses and explores potentials of Ayurveda in different aspects of uterine fibroid.